Dampak Penggunaan Game Blooket dengan Model Borg dan Gall Terhadap Minat Belajar Siswa pada Materi Fikih Muamalah di MTs Hidayatul Muhajirin - Hafizah Nuraini Ghani; Jasiah Jasiah (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study examines the impact of using the educational game Blooket, developed through the Borg and Gall model, on students' learning interest in the subject of Fiqh Muamalah at MTs Hidayatul Muhajirin. In the digital era, interactive learning methods such as educational games have become a popular choice to enhance student engagement. Blooket, as a game-based quiz platform, provides a fun and competitive learning environment. The research employs a case study approach with qualitative methods, involving interviews, observations, and documentation. The results indicate that the use of Blooket significantly enhances students' interest and understanding. Students became more enthusiastic about learning, as evidenced by increased participation, improved evaluation results, and active classroom discussions. Additionally, the Borg and Gall model facilitated the development of relevant and effective media tailored to students' needs. Despite challenges such as limited access to technology, the strengths of this medium in creating engaging learning experiences make it a modern solution for teaching challenging subjects like Fiqh Muamalah. The study concludes that technology-based innovations can increase learning interest if implemented effectively and supported by adequate facilities